(untitled) (Journal of Asian Development Studies, 2025)
Poverty, defined by insufficient income to cover basic needs, affects millions worldwide, particularly older adults. It has profound consequences on both physical and mental health, often resulting in disabilities, depression, and restricted social participation. This study explores older adults’ socioeconomic conditions, access to healthcare services, and how poverty influences their overall health and social integration. The research employs a phenomenological approach and convenience sampling to collect data from key informants, including older adults from local markets, roadsides, and labor workplaces in Muzaffarabad, Azad Jammu, and Kashmir. In-depth interviews were conducted with 20 older adults (all males), and the data was meticulously analyzed through a line-by-line coding process to derive key themes. derived from the coded information. The findings reveal that limited financial resources force elders to depend on modest pensions, occasional informal work, and support from family members and neighbors. Participants also reported experiencing social isolation due to financial limitations. Additionally, poverty severely impacted their health, further compounded by inadequate housing and living conditions. In conclusion, the study highlights the critical need to address the economic, social, and healthcare challenges older adults face to enhance their quality of life and ensure dignified aging in the region studied.